2017
DOI: 10.1002/ajmg.a.38291
|View full text |Cite
|
Sign up to set email alerts
|

Presynaptic congenital myasthenic syndrome with a homozygous sequence variant in LAMA5 combines myopia, facial tics, and failure of neuromuscular transmission

Abstract: Defects in genes encoding the isoforms of the laminin alpha subunit have been linked to various phenotypic manifestations, including brain malformations, muscular dystrophy, ocular defects, cardiomyopathy, and skin abnormalities. We report here a severe defect of neuromuscular transmission in a consanguineous patient with a homozygous variant in the laminin alpha-5 subunit gene (LAMA5). The variant c.8046C>T (p.Arg2659Trp) is rare and has a predicted deleterious effect. The affected individual, who also carrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 20 publications
0
33
0
Order By: Relevance
“…While mice deficient in the laminin α5 chain die in early embryogenesis, muscle‐specific knockout leads to delayed and incomplete postsynaptic maturation, suggestive of compromised interaction of laminin 521 with the postsynaptic receptor dystroglycan and a deficit in MuSK‐independent activation of AChR clustering (Miner et al, ; Montanaro et al, ; Nishimune et al, ). Recently identified loss‐of‐function mutations in LAMA5 are associated with underdevelopment and dysfunction of nerve terminals, leading to a severe CMS phenotype (Maselli et al, ; Maselli et al, ). While the α4 and α5 subunits are exclusively synaptic in the muscle, the α2 subunit can be incorporated into extrasynaptic laminin 211 in addition to the synaptic laminin 221, and mutations in its gene result in congenital muscular dystrophy both in mice and in man (Miyagoe‐Suzuki et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…While mice deficient in the laminin α5 chain die in early embryogenesis, muscle‐specific knockout leads to delayed and incomplete postsynaptic maturation, suggestive of compromised interaction of laminin 521 with the postsynaptic receptor dystroglycan and a deficit in MuSK‐independent activation of AChR clustering (Miner et al, ; Montanaro et al, ; Nishimune et al, ). Recently identified loss‐of‐function mutations in LAMA5 are associated with underdevelopment and dysfunction of nerve terminals, leading to a severe CMS phenotype (Maselli et al, ; Maselli et al, ). While the α4 and α5 subunits are exclusively synaptic in the muscle, the α2 subunit can be incorporated into extrasynaptic laminin 211 in addition to the synaptic laminin 221, and mutations in its gene result in congenital muscular dystrophy both in mice and in man (Miyagoe‐Suzuki et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…gene in the offspring of Trio11, which was predicted to have an effect on protein function by Polyphen-2 (Adzhubei et al, 2010), Provean (Choi, Sims, Murphy, Miller, & Chan, 2012), and SIFT (Kumar, Henikoff, & Ng, 2009; (Maselli et al, 2017). We also detected a causative de novo point mutation, was predicted by the above in silico tools, at NC_000016.9:g.18908115C > A (p.G86C) in the SMG1 (nonsense mediated mRNA decay associated PI3K related kinase) gene of Trio3 child (Table 2).…”
Section: Identification Of De Novo Mutationsmentioning
confidence: 77%
“…The child was born in 1982, and has expressed quadriplegia and mental retardation from an early age. A previous study identified a mutation on LAMA5 gene in a presynaptic congenital myasthenic syndrome patient, a disease characterized by muscle weakness and fatigability (Maselli et al., ). We also detected a causative de novo point mutation, was predicted by the above in silico tools, at NC_000016.9:g.18908115C > A (p.G86C) in the SMG1 (nonsense mediated mRNA decay associated PI3K related kinase) gene of Trio3 child (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…The calibration mark = 100 μM in E, 10 μM in F and G, 1 μm in H and I, and 2 μm in J and K. Modified with permission from Ref. .…”
Section: Clinical Reportmentioning
confidence: 99%
“…We recently reported an individual with a severe CMS attributed to a homozygous mutation in the gene encoding the laminin α5 subunit ( LAMA5 ) (MIM 601033), which showed selective presynaptic ultrastructural changes reminiscent of those found in the conditional Lama5 mutant mouse . In addition, the patient had physiologic changes similar to those seen in Lambert–Eaton myasthenic syndrome (LEMS).…”
Section: Introductionmentioning
confidence: 98%